Hubungan Self Disclosure dan Self Efficacy dengan Stres pada Mahasiswa Fakultas Keperawatan Universitas Riau dalam Menyusun Skripsi di Masa Pandemi Covid-19 - Putri, Syintya Eka; Jumaini; Sri Utami (Indonesian Journal of Nursing Research (IJNR), 2023)
Students in the process of working on a thesis are often faced with various problems that can cause stress. The stress felt by these students makes students do self-disclosure to get solutions or relieve their feelings and have high self-efficacy to turn obstacles into challenges so that students don't just give up in the face of obstacles in writing a thesis. Objective: to determine the relationship between self-disclosure and self-efficacy with stress on students of the Faculty of Nursing, University of Riau in compiling a thesis during the Covid-19 pandemic. Using descriptive correlation design, cross sectional approach. The research sample was 129 people using total sampling technique. Collecting data using a questionnaire that has been tested for validity and reliability. The analysis used is univariate analysis and bivariate analysis using chi-square test. The majority of respondents were 22 years old (62.8%), female gender (90.7%), self-disclosure to friends (71.3%), high self-disclosure (56.6%), high self-efficacy ( 54.3%) and moderate stress (71.3%). The results of the bivariate test have no relationship between self-disclosure and stress in students (p value 0.589 > = 0.05) and there is a significant relationship between self-efficacy and stress in students (p value 0.001 < = 0.05). There is no relationship between self-disclosure and stress and there is a relationship between self-efficacy and stress for students. Students in the process of working on the thesis are expected to carry out self-disclosure with full closeness and have high self-efficacy in order to overcome the stress they face.                                Abstrak Mahasiswa dalam proses pengerjaan skripsi seringkali dihadapkan pada berbagai masalah yang dapat menimbulkan stres. Stres yang dirasakan mahasiswa tersebut membuat mahasiswa melakukan keterbukaan diri untuk mendapatkan solusi atau meredakan perasaannya serta memiliki efikasi diri yang tinggi untuk mengubah hambatan menjadi tantangan sehingga mahasiswa tidak menyerah begitu saja dalam menghadapi hambatan dalam penulisan skripsi. Tujuan: untuk mengetahui hubungan self-disclosure dan self-efficacy dengan stres pada mahasiswa Fakultas Keperawatan Universitas Riau dalam menyusun skripsi di masa pandemi Covid-19. Menggunakan desain deskriptif korelasi, pendekatan cross sectional. Sampel penelitian sebanyak 129 orang dengan menggunakan teknik total sampling. Pengumpulan data menggunakan kuesioner yang telah diuji validitas dan reliabilitasnya. Analisis yang digunakan adalah analisis univariat dan analisis bivariat dengan menggunakan uji chi-square. Mayoritas responden berusia 22 tahun (62,8%), jenis kelamin perempuan (90,7%), keterbukaan diri kepada teman (71,3%), keterbukaan diri tinggi (56,6%), efikasi diri tinggi (54,3%) dan stres sedang. (71,3%). Hasil uji bivariat tidak ada hubungan antara self-disclosure dengan stres pada mahasiswa (p value 0,589 > = 0,05) dan ada hubungan yang signifikan antara self-efficacy dengan stres pada mahasiswa (p value 0,001 < = 0,05). Tidak ada hubungan antara self-disclosure dengan stres dan ada hubungan antara self-efficacy dengan stres pada siswa. Mahasiswa dalam proses pengerjaan skripsi diharapkan dapat melakukan keterbukaan diri dengan penuh keakraban dan memiliki efikasi diri yang tinggi guna mengatasi stres yang dihadapinya.